Serum Dipeptidyl peptidase-4 level is related to adiposity in type 1 diabetic adolescents. Issue 4 (July 2020) - Ibrahim, Amany; Salah, Shaimaa; Attia, Mona; Madani, Hanan; Ahmad, Samah; Arafa, Noha; Soliman, Hend
Abstract: Background: Insulin resistance (IR) plays a great role in type 1 diabetes (T1DM) disease process than is commonly recognized. Dipeptidyl peptidase-4 (DPP-4) is an enzyme that deactivates many bioactive peptides involved in glucose regulation. Aims: This study evaluates DPP-4 level in adolescent patients with T1DM compared to controls and investigates the relationship between DPP-4 level and IR in these patients. Materials and methods: We measured serum DPP-4 level in 50 patients with T1DM recruited from the Diabetes Endocrine Metabolism Pediatric Unit, and in 80 healthy controls. IR was assessed by the equation for estimated glucose disposal rate (eGDR). Biochemical evaluation including glycated haemoglobin (HbA1C) and lipid profile were included. Results: IR was found in 80% of patients with T1DM. DPP-4 was significantly higher in control group than patients with T1DM. Patients with T1DM were classified into 3 groups according to DPP-4 tertiles showing significant increase in BMI SDS and total cholesterol across the 3 groups. Significant correlation was found between DPP-4 levels and insulin dose. DPP-4 was significantly higher in patients with T1DM with good glycemic control. Conclusion: In sample of individuals researched by us, serum DPP-4 was related to adiposity and not to the hyperglycemia in patients with T1DM. Larger sample should be researched to make firm conclusions. Highlights: We measured serum DPP-4 level in 50 patients with T1DM and in 80 healthy controls. DPP-4 levels are higher in control group, in T1DM patients with good glycemic control and in non-dyslipidemic T1DM patients. Serum DPP-4 levels in our sample of patients is related to the state of adiposity.